2017
DOI: 10.7759/cureus.1173
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable Analysis of Factors Affecting Length of Stay and Hospital Charges After Atlantoaxial Fusion

Abstract: BackgroundAtlantoaxial fusion is an effective procedure for treating degenerative, traumatic, and congenital abnormalities that result in upper cervical instability; however, data on which factors affect the length of stay and hospitalization-related charges are limited. The purpose of this study was to evaluate the pre-, intra-, and postoperative variables that affect these healthcare cost factors for patients undergoing posterior atlantoaxial fusion.MethodsWe retrospectively identified from a clinical databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Our results suggest that a more stringent overlapping surgery policy did not lead to cost savings in our cohort, and overlapping surgery was not associated with higher or lower costs in and of itself. The variables that did appear to lead to higher hospitalization costs were largely unsurprising-complications, 5,12 emergency surgery, 11 operating room time, 15 surgery type, 6 inability to discharge home, 17 higher ASA class, 19 and tobacco use 10,16 -and have all previously been shown to be significantly associated with hospital costs. Our finding that preoperative steroid use was associated with lower costs was somewhat surprising, although some evidence suggests that such use may reduce length of stay in patients undergoing crani- otomy for tumor, which may partially explain this association.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that a more stringent overlapping surgery policy did not lead to cost savings in our cohort, and overlapping surgery was not associated with higher or lower costs in and of itself. The variables that did appear to lead to higher hospitalization costs were largely unsurprising-complications, 5,12 emergency surgery, 11 operating room time, 15 surgery type, 6 inability to discharge home, 17 higher ASA class, 19 and tobacco use 10,16 -and have all previously been shown to be significantly associated with hospital costs. Our finding that preoperative steroid use was associated with lower costs was somewhat surprising, although some evidence suggests that such use may reduce length of stay in patients undergoing crani- otomy for tumor, which may partially explain this association.…”
Section: Discussionmentioning
confidence: 99%
“…4 Guan et al similarly found that between 2010 and 2015, 41% of AA fusions at a single institution were performed secondary to fracture. 7 Patients admitted due to trauma have been found to incur higher hospital charges during their stay, likely due to inherently higher costs associated with emergency care. 8,10 This may account for the rise in hospital costs and charges seen in tandem with an increase in AA fusion rates and an increase in those procedures indicated for trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid conditions, such as anemia, anxiety diagnosis, high body mass index, diabetes mellitus (DM), illness severity, intraoperative complications after surgery, and multilevel fusion procedures can also impact LOS. 7,8 Many studies have analyzed LOS in ALIF patients as the dependent variable in conjunction with PROMs. However, no studies have used LOS as a comparison variable.…”
Section: Introductionmentioning
confidence: 99%